High temperature resistant coated sand for steel casting and preparation method thereof
By combining inorganic flame retardant materials with polyhydroxy surfactants into composite additives in coated sand for cast steel, combining regeneration of Hainan sand and phenolic resin, the heat resistance performance of existing coated sand for cast steel at high temperatures is solved. and the problem of insufficient strength achieves more efficient casting performance and environmentally friendly resource recycling.
Patent Information
- Application Number
- CN202211672917.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-12-26
AI Technical Summary
The existing coated sand for cast steel is insufficient in heat resistance and strength at high temperatures, resulting in casting defects, especially when the casting weight exceeds 50 kg and the wall thickness is large.
Inorganic flame retardant materials and polyhydroxy surfactants are used to combine them into composite additives, and combined with regenerated Hainan sand and phenolic resins to prepare high-temperature-resistant coated sand for cast steel. The composite additives include white corundum, expanded graphite, high alumina cerite and surfactant. Through the material decomposition and thermal flame retardant mechanism, the heat resistance and strength of the sand type are improved.
It significantly improves the heat resistance and strength of the coated sand, can effectively prevent metal liquid from penetrating into the sand, reduce the occurrence of casting defects, and has the advantages of environmental protection and cost-effectiveness through resource recycling.
Smart Images

Figure DEST_PATH_IMAGE001
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coated sand, and in particular relates to high temperature resistant coated sand for steel casting and a preparation method thereof. Background Art
[0002] my country began to study and apply the coated sand and shell core technology for casting in the 1950s. With the continuous improvement of raw materials, manufacturing equipment and manufacturing processes, the quality of coated sand for casting has been continuously improved, and the production cost has gradually decreased. Since the 1990s, its application has been developed more rapidly, the variety of products has been increasing, and it has formed a series. At present, the annual production and sales volume of my country's foundry coated sand industry has reached more than 2 million tons, with a wide variety and complex models. Because the temperature of cast iron products is low during pouring, the heat resistance of coated sand shell molds is not high, and coated sand is widely used in cast iron parts. However, cast steel products have higher requirements for the heat resistance of coated sand shell molds, especially cast steel products with a weight of more than 50 kilograms and thick walls. At present, most foundries still use precision casting to produce them.
[0003] At present, the raw sand for coated sand usually uses natural high-silicon Hainan sand with a silicon content of more than 98%. Natural silica sand is a non-renewable resource and cannot be completely recycled into cast steel products after being regenerated by thermal and mechanical methods. The flammability of ordinary phenolic resin is generally considered to be between flammable and flame retardant: at about 130°C, the resin further cross-links, the hydroxymethyl groups that do not participate in the curing and cross-linking are oxidized and removed, and the ether bond breaks; at about 450°C, the methylene bridge between the phenolic hydroxyl group and the benzene ring breaks, and the pyrolysis products are benzene and phenol homologues, and pyrolysis intermediates such as xanthenes appear. At the same time, the methylene group is oxidized to carboxyl groups and dehydrogenated to carbon at high temperatures. The phenolic hydroxyl group and methylene group of phenolic resin are easily oxidized, and thermal decomposition and oxidative decomposition occur at high temperatures at the same time. The oxidative decomposition is particularly significant, forming partial carbonization, affecting heat resistance, and reducing the strength of the sand mold. If the molten steel in contact with the sand mold has not solidified, and the connecting bridge between the sand particles has been completely decomposed, the molten metal will penetrate into the sand mold through the gaps between the sand particles, forming casting defects.
[0004] By adding additives to the coated sand system, its heat resistance when used in cast steel products can be improved. For example, adding graphite during the mixing process of coated sand is to utilize the oxidation of graphite to decompose into CO 2and CO, forming an air film on the surface of the sand mold to prevent the metal liquid from penetrating into the sand mold. However, the amount of graphite added to the coated sand is very small, mostly 0.2%-0.5% (accounting for the mass fraction of the aggregate), and its effect is limited. Too much addition will affect the strength of the coated sand. Adding ferroferric oxide to increase the thermal conductivity of the sand mold can only play an auxiliary role and cannot directly improve the heat resistance of the coated sand. Adding high-melting-point powders such as zircon powder, corundum powder, and bauxite can increase the melting point of the aggregate, but after the resin layer on the surface of the aggregate burns and decomposes, mechanical sand adhesion will be formed, affecting the performance of the coated sand. Summary of the invention
[0005] The purpose of the present invention is to provide a high-temperature resistant coated sand for cast steel in view of the above technical problems, which is compounded with inorganic flame retardant materials into a composite additive to improve the heat resistance and strength of the coated sand. It can be used for cast steel products with a casting weight of more than 50 kilograms and a thick wall.
[0006] The high temperature resistant coated sand for cast steel in the technical solution of the present invention comprises the following components in parts by weight: 150-200 parts of aggregate, 5-10 parts of phenolic resin, 0.3-0.8 parts of composite additives, 1.0-5.0 parts of curing agent, and 0.3-0.6 parts of lubricant.
[0007] Furthermore, the aggregate includes 90-95% of recycled Hainan sand and 5-10% of iron sand.
[0008] Furthermore, the regenerated Hainan sand is obtained by recycling the waste sand after the Hainan original sand is used to make the coated sand casting, and regenerating it. For the specific regeneration method, refer to patent CN109822044A. The secondary low-temperature roasting of the intermittent combustion roasting furnace is combined with the mechanical combined regeneration equipment, and the low-temperature roasting principle is adopted. The high temperature of the hot sand after roasting is fully reversed with the normal temperature flowing air supplied to the furnace for combustion, and the secondary heat source generated by the combustion of residual carbon is used for roasting. The waste heat of the roasting reaction and the heat of cooling the hot sand are preheated through the countercurrent heat exchanger in front of the furnace to obtain the regenerated Hainan sand of resin core sand and clay mixed old sand with excellent quality.
[0009] Furthermore, the mesh size of the regenerated Hainan sand is 70~140 mesh.
[0010] Furthermore, the composite additive includes 30-40% white corundum, 20-30% expanded graphite, 25-35% high-alumina pyrophyllite and 10-15% surfactant.
[0011] White corundum has a dense structure, small thermal expansion, and is an amphoteric oxide with strong acid and alkali resistance. It does not react with the poured metal liquid, and its thermal performance is higher than that of zircon powder materials. It can be used to make coated sand auxiliary materials to improve the heat resistance of coated sand and prevent sand sticking defects in castings. Expandable graphite can form a dense and stable expansion layer, which has the functions of heat insulation and oxygen isolation. It can block the transfer of heat and material between heat and substrate, delay or inhibit the thermal degradation or thermal oxidation degradation of polymers, and finally achieve the purpose of flame retardancy. It absorbs a large amount of environmental heat during the expansion process, which can reduce the temperature of the system. High-aluminum pyrophyllite is dense and smooth, and has lubricity. It can be evenly distributed in the coating process of phenolic resin on the surface of sand particles. Its own refractory temperature is as high as 1710℃, and it also has a certain flame retardant function. There is a balanced endothermic reaction valley between 600~700℃, and no exothermic reaction peak appears at 1000℃. This is because the structure of pyrophyllite is not destroyed after dehydration, and no new crystallization and combination occur.
[0012] Furthermore, the mesh number of white corundum is 300~400 mesh.
[0013] Furthermore, the mesh number of the expanded graphite is 150-800 meshes.
[0014] Furthermore, the mesh number of the high-alumina pyrophyllite is 200-500 mesh.
[0015] Furthermore, the surfactant includes a polyhydroxy surfactant, which can be listed as one or more of sorbitol, glyceryl monostearate, sorbitan fatty acid, and polysorbate.
[0016] The polyhydroxyl groups in the surfactant can produce good hydrogen bonding with the hydroxyl groups in the phenolic resin, thereby strengthening the bonding force between the composite additive and the phenolic resin, and at the same time facilitating the uniform distribution of the composite additive in the phenolic resin.
[0017] Furthermore, the curing agent is a solution of hexamethylenetetramine (urotropine) and water in a mass ratio of 1.0:1.5-3.0.
[0018] Furthermore, the lubricant is one or more of calcium stearate, stearic acid, and glyceryl stearate.
[0019] The present invention also provides a method for preparing the above-mentioned high temperature resistant coated sand for steel casting, comprising the following steps:
[0020] (1) white corundum, expanded graphite, high-aluminum pyrophyllite and a surfactant are mixed to obtain a composite additive slurry;
[0021] (2) After the aggregate is heated, phenolic resin and composite additive slurry are added in sequence, a curing agent is added for curing, and then a lubricant is added. The aggregate is crushed, sieved, and cooled to obtain high-temperature resistant coated sand for steel casting.
[0022] Furthermore, in step (2), the aggregate is heated to 130-150°C.
[0023] Furthermore, in step (2), the phenolic resin and composite additive slurry are added and stirred for 40 to 60 seconds.
[0024] Furthermore, before adding the curing agent in step (2), 0°C water is first added to cool the system to prevent rapid curing due to excessively high system temperature when the curing agent is added.
[0025] Furthermore, the curing time in step (2) is 50 to 70 seconds.
[0026] Furthermore, in step (2), the lubricant is added and stirred for 20 to 30 seconds.
[0027] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0028] (1) The present invention uses an inorganic flame retardant material and a polyhydroxy surfactant to form a composite additive for coated sand, and utilizes the material decomposition endothermic flame retardant mechanism to slow down the combustion and decomposition time of the phenolic resin after curing, thereby improving the heat resistance and strength of the coated sand;
[0029] (2) Aggregates are made of recycled Hainan sand, which is a type of resource recycling and reuse, environmentally friendly and highly cost-effective, and can be widely promoted and used in the market;
[0030] (3) White corundum has strong acid and alkali resistance, does not react with the poured metal liquid, and has higher thermal performance than zircon powder material, which can prevent sand sticking defects in castings;
[0031] (4) Expandable graphite can form a dense and stable expansion layer, which has the function of heat insulation and oxygen isolation, can block the heat transfer in the coated sand system, and delay or inhibit the thermal degradation or thermal oxidation degradation process of the polymer;
[0032] (5) High-alumina pyrophyllite will undergo an endothermic reaction at high temperatures, with a low volume expansion rate, which can improve the strength and heat resistance of coated sand;
[0033] (6) The hydroxyl groups in the surfactant can produce a certain hydrogen bonding effect with the hydroxyl groups in the phenolic resin, thereby strengthening the binding force between the composite additive and the phenolic resin, and at the same time facilitating the uniform distribution of the composite additive in the phenolic resin;
[0034] (7) The high temperature resistant coated sand for steel casting obtained by the technical solution of the present invention can be used for steel casting products with a casting weight exceeding 50 kg and a thick wall. DETAILED DESCRIPTION
[0035] The technical scheme of the present invention is further described below by specific embodiments. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not intended to be used for specific limitations of the present invention. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0036] The regeneration method of the regenerated Hainan sand used in the following embodiments and comparative examples is specifically that the feeding equipment group feeds the waste sand from the waste sand inlet at the top of the roasting furnace. After the waste sand is fed in, it contacts the sand separator and is sprinkled in the furnace body in a rain-like manner. The waste sand burns during the falling process, and the airflow in the bellows goes upward along the heat exchanger. At the outlet at the top of the heat exchanger, the waste sand completes one roasting. The sand after the one roasting continues to fall, and falls along the outer wall of the heat exchanger during the falling process. At the same time, it relies on the heat carried by the sand itself for a second roasting to completely burn the remaining combustibles. After falling onto the sand falling plate, it falls along the discharge pipe and is finally discharged from the roasting product discharge port. The discharge processing equipment group separates the particle size of the roasting product and cools it to reach the output temperature.
[0037] Example 1
[0038] The method for preparing high temperature resistant coated sand for steel casting in this embodiment comprises the following steps:
[0039] (1) 0.3 parts of white corundum, 0.3 parts of expanded graphite, 0.25 parts of high-alumina pyrophyllite and 0.15 parts of polysorbate were stirred and mixed to obtain a composite additive slurry;
[0040] (2) Weigh 172 parts of aggregate (160 parts of recycled Hainan sand and 12 parts of iron sand), heat to 138°C and put into a mixing equipment, add 5 parts of phenolic resin and 0.5 parts of composite additive slurry, stir for 60 seconds, first add 0°C water, then add 2.0 parts of curing agent mixed with hexamethylenetetramine and water in a mass ratio of 1.0:2.0, and stir for 70 seconds;
[0041] (3) Add 0.3 parts of calcium stearate and stir for 30 seconds to disperse the lumps to form coated sand particles. Crush, sieve and cool to obtain high temperature resistant coated sand for steel casting.
[0042] Example 2
[0043] The method for preparing high temperature resistant coated sand for steel casting in this embodiment comprises the following steps:
[0044] (1) 0.3 parts of white corundum, 0.3 parts of expanded graphite, 0.25 parts of high-alumina pyrophyllite and 0.15 parts of glyceryl monostearate were stirred and mixed to obtain a composite additive slurry;
[0045] (2) Weigh 172 parts of aggregate (163 parts of recycled Hainan sand and 9 parts of iron sand), heat to 145°C and put into a mixing equipment, add 6 parts of phenolic resin and 0.5 parts of composite additive slurry, stir for 60 seconds, first add 0°C water, then add 2.5 parts of curing agent mixed with hexamethylenetetramine and water in a mass ratio of 1.0:2.0, and stir for 70 seconds;
[0046] (3) Add 0.5 parts of calcium stearate and stir for 30 seconds to disperse the lumps to form coated sand particles. Crush, sieve and cool to obtain high temperature resistant coated sand for steel casting.
[0047] Example 3
[0048] The method for preparing high temperature resistant coated sand for steel casting in this embodiment comprises the following steps:
[0049] (1) 0.35 parts of white corundum, 0.35 parts of expanded graphite, 0.2 parts of high-alumina pyrophyllite and 0.1 parts of sorbitol were stirred and mixed to obtain a composite additive slurry;
[0050] (2) Weigh 172 parts of aggregate (155 parts of recycled Hainan sand and 17 parts of iron sand), heat to 145°C and put into a mixing equipment, add 5 parts of phenolic resin and 0.6 parts of composite additive slurry, stir for 50 seconds, first add 0°C water, then add 2.5 parts of curing agent mixed with hexamethylenetetramine and water in a mass ratio of 1.0:2.0, and stir for 60 seconds;
[0051] (3) Add 0.5 parts of calcium stearate and stir for 30 seconds to disperse the lumps to form coated sand particles. Crush, sieve and cool to obtain high temperature resistant coated sand for steel casting.
[0052] Example 4
[0053] The difference between this embodiment and embodiment 1 is that step (1) is to stir and mix 0.3 parts of white corundum, 0.3 parts of expanded graphite, 0.25 parts of high-alumina pyrophyllite and 0.25 parts of polysorbate to obtain a composite additive slurry.
[0054] Example 5
[0055] The difference between this embodiment and embodiment 1 is that step (1) is to stir and mix 0.3 parts of white corundum, 0.3 parts of expanded graphite, 0.25 parts of high-alumina pyrophyllite and 0.05 parts of polysorbate to obtain a composite additive slurry.
[0056] Comparative Example 1
[0057] The difference between this comparative example and Example 1 is that step (1) is to stir and mix 0.45 parts of expanded graphite, 0.4 parts of high-alumina pyrophyllite and 0.15 parts of polysorbate to obtain a composite additive slurry.
[0058] Comparative Example 2
[0059] The difference between this comparative example and Example 1 is that step (1) is to stir and mix 0.45 parts of white corundum, 0.4 parts of high-alumina pyrophyllite and 0.15 parts of polysorbate to obtain a composite additive slurry.
[0060] Comparative Example 3
[0061] The difference between this comparative example and Example 1 is that step (1) is to stir and mix 0.45 parts of white corundum, 0.4 parts of expanded graphite and 0.15 parts of polysorbate to obtain a composite additive slurry.
[0062] Comparative Example 4
[0063] The difference between this comparative example and Example 1 is that step (1) is to stir and mix 0.85 parts of white corundum and 0.15 parts of polysorbate to obtain a composite additive slurry.
[0064] Comparative Example 5
[0065] The difference between this comparative example and Example 1 is that step (1) is to stir and mix 0.85 parts of expanded graphite and 0.15 parts of polysorbate to obtain a composite additive slurry.
[0066] Comparative Example 6
[0067] The difference between this comparative example and Example 1 is that step (1) is to stir and mix 0.85 parts of high-alumina pyrophyllite and 0.15 parts of polysorbate to obtain a composite additive slurry.
[0068] Comparative Example 7
[0069] The difference between this comparative example and Example 1 is that step (1) is to stir and mix 0.3 parts of white corundum, 0.3 parts of expanded graphite, 0.25 parts of high-alumina pyrophyllite and 0.15 parts of sodium dodecylbenzene sulfonate to obtain a composite additive slurry.
[0070] Comparative Example 8
[0071] The preparation method of the coated sand in this comparative example comprises the following steps:
[0072] (1) Weigh 172 parts of aggregate (160 parts of recycled Hainan sand and 12 parts of iron sand), heat to 138°C and put into a mixing equipment, add 5 parts of phenolic resin and 0.5 parts of composite additives, and stir for 60 seconds. The composite additives are 0.35 parts of white corundum, 0.35 parts of expanded graphite, and 0.3 parts of high-alumina pyrophyllite;
[0073] (2) First add 0°C water, then add 2.0 parts of a curing agent mixed with hexamethylenetetramine and water in a mass ratio of 1.0:2.0, and stir for 70 seconds;
[0074] (3) Add 0.3 parts of calcium stearate and stir for 30 seconds to disperse the lumps to form coated sand particles. Crush, sieve and cool to obtain high temperature resistant coated sand for steel casting.
[0075] Comparative Example 9
[0076] The preparation method of the coated sand in this comparative example comprises the following steps:
[0077] (1) Weigh 172 parts of aggregate (160 parts of recycled Hainan sand and 12 parts of iron sand), heat to 138°C and put into a mixing equipment, add 5 parts of phenolic resin and 0.5 parts of dimethyl methylphosphonate, and stir for 60 seconds;
[0078] (2) First add 0°C water, then add 2.0 parts of a curing agent mixed with hexamethylenetetramine and water in a mass ratio of 1.0:2.0, and stir for 70 seconds;
[0079] (3) Add 0.3 parts of calcium stearate and stir for 30 seconds to disperse the lumps to form coated sand particles. Crush, sieve and cool to obtain high temperature resistant coated sand for steel casting.
[0080] Comparative Example 10
[0081] The preparation method of the coated sand in this comparative example comprises the following steps:
[0082] (1) Weigh 172 parts of aggregate (160 parts of recycled Hainan sand and 12 parts of iron sand), heat to 138°C and put into a mixing equipment, add 0.7 parts of earthy graphite powder and 5 parts of phenolic resin, and stir for 50 seconds;
[0083] (2) First add 0°C water, then add 2.0 parts of a curing agent mixed with hexamethylenetetramine and water in a mass ratio of 1.0:2.0, and stir for 60 seconds;
[0084] (3) Add 0.3 parts of calcium stearate and stir for 30 seconds to disperse the lumps to form coated sand particles. Crush, sieve and cool to obtain high temperature resistant coated sand for steel casting.
[0085] The coated sand obtained in the above embodiments and comparative examples was tested for room temperature tensile strength, hot tensile strength, room temperature flexural strength, hot flexural strength, gas evolution, ignition loss and heat resistance time. The test results are shown in Table 1 below.
[0086] Table 1 Performance data of coated sand obtained in Examples and Comparative Examples
[0087]
[0088] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A high temperature resistant coated sand for steel casting, characterized in that: The invention comprises the following components in parts by weight: 150-200 parts of aggregate, 5-10 parts of phenolic resin, 0.3-0.8 parts of composite additives, 1.0-5.0 parts of curing agent, and 0.3-0.6 parts of lubricant; the aggregate comprises 90-95% of recycled Hainan sand and 5-10% of iron sand; The composite additive includes 30-40% white corundum, 20-30% expanded graphite, 25-35% high-aluminum pyrophyllite and 10-15% surfactant; the surfactant includes a polyhydroxy surfactant; the curing agent is a solution of hexamethylenetetramine and water mixed in a mass ratio of 1.0:1.5-3.0; the lubricant is one or more of calcium stearate, stearic acid and stearyl glyceride.
2. The high temperature resistant coated sand for steel casting according to claim 1, characterized in that: The mesh size of regenerated Hainan sand is 70~140 mesh.
3. The high temperature resistant coated sand for steel casting according to claim 1, characterized in that: The mesh number of white corundum is 300~400 mesh.
4. The high temperature resistant coated sand for steel casting according to claim 1, characterized in that: The mesh size of expanded graphite is 150~800 mesh.
5. The high temperature resistant coated sand for steel casting according to claim 1, characterized in that: The mesh size of high-alumina pyrophyllite is 200~500 mesh.
6. A method for preparing high temperature resistant coated sand for steel casting as claimed in claim 1, characterized in that: The following steps are involved: (1) white corundum, expanded graphite, high-aluminum pyrophyllite and a surfactant are mixed to obtain a composite additive slurry; (2) After the aggregate is heated, phenolic resin and composite additive slurry are added in sequence, a curing agent is added for curing, and then a lubricant is added. The aggregate is crushed, sieved, and cooled to obtain high-temperature resistant coated sand for steel casting.
Citation Information
Patent Citations
Production line of reclaimed sand
CN109822044A
Coated sand and preparation method thereof
CN104325065A
High-temperature-resistant precoated sand and preparation method thereof
CN114367629A